Role pf PPARalpha in the cardiac metabolic adaptation to chronic hypoxia - Abd Jamil, AH (2012)
The principal substrate used by the normal adult human heart is free fatty acids, the remainder being, predominantly,carbohydrate. During failure, the heart becomes less reliant on fatty acid metabolism, possibly as a result of tissue hypoxia. Therefore, understanding hypoxic adaptation may explain the metabolic changes that occur during the development of heart failure.As peroxisome proliferator activated receptor alpha (PPARα) modulates cardiac fatty acid metabolism, the work in this thesis focused on the role of PPARα in cardiac metabolic adaptation to chronic hypoxia. It was found that isolated hearts from chronically hypoxic (11% O2 for 3 weeks)mice were more glycolytic, had reduced PPARα expression and decreased fatty acid metabolism,but had normal function, determined using in vivocine-MRI. 31P MRS of isolated perfused mouse hearts showed a drop in PCr with hypoxia, but ΔGATP was not altered, indicating that metabolic reprogramming was sufficient to maintain ATP production and contractile function. Increased or decreasedPPARα expression, using a high fat diet or PPARα null mice, respectively, prevented metabolic adaptation to hypoxia and caused cardiac dysfunction. Hypoxia with high fat feeding was particularly deleterious, reducing ejection fraction by 9%,possibly due to increased mitochondrial uncoupling. PPARβ/δ and γ were not involved in the adaptation to hypoxia, and none were modified by PPARα stimulation or ablation. Cardiac VEGF and PDK1, prominent hypoxia-inducible factor (HIF) targets, were increased by hypoxia, indicating that HIF may have been involved in metabolic adaption. However, high fat feeding prevented VEGF accumulation during hypoxia, suggesting that impaired HIF signalling may have contributed to the maladaptive response to hypoxia. In order to determine the relationship between HIF and PPARα, HIFwas stabilised pharmacologically using FG2216/BIC in HL-1 cardiomyocytes, to show decreased PPARα expression and caused similar metabolic changes to those seen in the in vivo hypoxic heart. In conclusion, this study demonstrated that HIF downregulation of PPARα is crucial for metabolic adaptation and maintenance of cardiac function during chronic hypoxia. Similar metabolic changes that occur in end-stage heart failure may also be a response to increasing hypoxia.